Women and leadership: what is the noise all about? (2000)
The controversy surrounding the issue of women and leadership position is as old as the history and creation of women itself. The issue, if not "liberation of women" from whatever perceived bondage, would be that of "equality with men", or of recent that of "women empowerment". This controversy would be this heated up if the creation of women and their assigned roles is traced from biblical injunction and that, which is naturally and socially determined. A woman, though as a human being may aspire to whatever height in any chosen field she so desires, should not do so at the expense of the role assigned her by nature for which she is best suited. This view is what the paper would attempt to elucidate to show why energy should not be dissipated on whether women should ''fight'' what should be the norm rather than exception on leadership matters. After all, what is leadership if placed in its right perspective?